Credit Card Redlining - Cohen-Cole, Ethan (The Review of Economics and Statistics, 2011)
This paper evaluates the presence of racial disparities in the issuance of consumer credit. Using a database of credit histories, I link location-based information on race with individual credit files. After controlling for place-specific factors such as housing vacancy rates and general population demographics, I find qualitatively large differences in the amount of credit offered to similarly qualified applicants living in black versus white areas. High data quality allows distinguishing between issuer-provision (supply) and utilization of credit (demand). Additional estimates using information on payday lending provide support for idea that issuers condition lending on location.